2019
DOI: 10.1051/matecconf/201929006004
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on the role of modernizing the road infrastructure in the prevention of road accidents

Abstract: The realizing and improvement of road infrastructure, of modern road networks provides normal, safe and pleasant road traffic conditions and also help prevent road accidents. The road network, with its constructive characteristics, has to offer optimal conditions for the movement of vehicles, pedestrians and other categories of participants in the road traffic. Starting from the case study of a road sector with heavy road traffic, the current paper analyzes the increase in road safety in Romanian localities al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In Romania, 60% of road traffic accidents were caused by road alignment (Cioca & Ivascu 2017). This was further corroborated by Cristian and Lucian (2019), who concluded that road design has a significant bearing on road safety. Their study, also done in Romania, revealed that the construction of sidewalks, expanding the number of lanes in certain sections of the road and elevating pedestrian crossings reduced the occurrence of road traffic accidents.…”
Section: Road Infrastructurementioning
confidence: 73%
“…In Romania, 60% of road traffic accidents were caused by road alignment (Cioca & Ivascu 2017). This was further corroborated by Cristian and Lucian (2019), who concluded that road design has a significant bearing on road safety. Their study, also done in Romania, revealed that the construction of sidewalks, expanding the number of lanes in certain sections of the road and elevating pedestrian crossings reduced the occurrence of road traffic accidents.…”
Section: Road Infrastructurementioning
confidence: 73%
“…As is true of all road structures, there are the danger of falling accidents due to aging [2]. Traffic infrastructure has been changing to prevent accidents [3]. Road manager do not want to place heavy electrical equipment overhead for driver's safety reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Road cycling is an endurance sport in which athletes ride their bicycles on courses that mainly contain public roads. The number of vehicles using these public roads is slowly increasing through the years [5] and as a side effect the amount of traffic incidents is also increasing. Safety measures such as traffic calming infrastructure, roundabouts or speed bumps [7,8,11] on public roads are often introduced to cope with this issue and have a significant impact on the number of road fatalities [6].…”
Section: Introductionmentioning
confidence: 99%